2021
DOI: 10.1002/ldr.4069
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal dynamics in soil iron affected by wetland conversion on the Sanjiang Plain

Abstract: Since the 1950s, nearly 80% of wetlands in the Sanjiang Plain have been converted into paddy fields. The conversion might affect the solubility and mobility of soil iron, influencing the export of iron into the Amur River and the primary production of the Okhotsk Sea. However, information regarding long-term studies of the spatiotemporal dynamics of soil iron after cultivation is limited. In this study, six regions, including 18 plots in the Sanjiang Plain, were selected as sampling sites covering natural wetl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…The driver behind this trend was the change in the crop planting structure, with a decline in dry land and the expansion of paddy fields (Wang et al 2014; Zhang et al 2022). Moreover, it has been previously reported that paddy fields have replaced ∼80% of the wetlands since the 1950 s (Chi et al 2021). Figure 8b shows that cumulative GWSV exhibited a linear downward trend from 2000 to 2017, thereby indicating that groundwater storage presented a long‐term decrease.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The driver behind this trend was the change in the crop planting structure, with a decline in dry land and the expansion of paddy fields (Wang et al 2014; Zhang et al 2022). Moreover, it has been previously reported that paddy fields have replaced ∼80% of the wetlands since the 1950 s (Chi et al 2021). Figure 8b shows that cumulative GWSV exhibited a linear downward trend from 2000 to 2017, thereby indicating that groundwater storage presented a long‐term decrease.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, rice is the dominant crop (Song et al 2008; Wang et al 2014) in the Sanjiang Plain. The acreage of paddy fields increased (Chi et al 2021; Zhang et al 2022) over the years, thereby increasing the amount of groundwater exploitation.…”
Section: Resultsmentioning
confidence: 99%
“…Although only 0.72% water samples had NO 2 − content above the permissible limit, the over-limit ratio of NH 3 -N is up to 25.48%, according to the Chinese drinking water standard. However, groundwater's Fe concentrations in this area reached high levels because of their geochemical nature [54]. Therefore, NO 3 -N and NH 3 -N were identified as the major anthropogenic pollutants in the study area.…”
Section: Groundwater Quality For Drinkingmentioning
confidence: 89%
“…Studies have shown that soil organic matter can promote activation, solubility, and migration of soil Fe through reduction and complexation in an anaerobic environment (Jansen et al, 2003;Giannetta et al, 2020). Chi et al (2021) studied the temporal dynamics in soil Fe affected by wetland conversion on the Sanjiang Plain and the results indicated that soil Fe stock in the 0-120 cm layers gradually increased with increasing planting ages within 18 yr and the decrease in SOC contributed to the changed transportation and dynamics of soil Fe after wetland conversion. In comparison, the acidic environment under an anaerobic condition was conducive to promoting the solubility, mobility, and leaching loss of Fe in the soil (Gotoh and Patrick, 1974;Schwertmann, 1985).…”
Section: Variations and Controls Of Fe Loss During Paddy Soil Evolutionmentioning
confidence: 99%